Apoyo a la preparación y presentación de información exógena año 2013 Controlaría General del Quindío (2014)
The Colombian government regulates both natural and legal persons through obligations introduced in the law, for such work it designates a special administrative unit; known as DIAN , which aims to ensure fiscal security of the Colombian state and the protection of national economic order , by administrating and controlling the compliance with tax obligations , who through decrees , reforms, resolutions and regulations tax, determine the required group ( government entities , natural persons, legal persons ) to meet the obligations to which they find themselves subjected.